THE EFFECT OF CONVENIENCE, PROMOTION AND BENEFITS ON THE DECISION TO USE A DIGITAL PAYMENT SYSTEM IN GENERATION Y IN LHOKSEUMAWE CITY - Rosa Zachrul Phonna; Sapna Biby; Mohd Heikal; Rahmaniar (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
The purpose of this study was to determine the magnitude of the influence of convenience, promotion and benefits on decisions to use digital payment systems in generation Y in the city of Lhokseumawe. The subject of this research is generation Y or millennial generation in Lhokseumawe city. The sample in this study amounted to 138 respondents. The data collection technique used is a questionnaire. The author distributed questionnaires to 138 respondents of generation Y or millennials in the city of Lhokseumawe who use digital payment systems. The value of the correlation coefficient (R) is 0.644 and the Adjusted R2 value is 0.520 or 50.2% and the remaining 49.8% is influenced by other factors outside this research model (error term). From the partial test results, the three independent variables namely convenience (X1) has a value of tcount (4,040) > ttable (1,977), promotion (X2) has a value of tcount (7.219) > ttable (1,977) and benefits (X3) have a value of tcount ( 4,123) > ttable (1,977). So it can be concluded that convenience (X1), promotion (X2) and benefits (X3) partially influence the decision to use (Y). For simultaneous or concurrent testing (Test F), convenience (X1), promotion (X2) and benefits (X3) significantly influence the decision to use (Y) digital payment systems in generation Y in Lhokseumawe city because the value of Fcount (31,614) > Ftable (2.67). And for the most dominant variable influencing the decision to use is promotion (X2) with tcount (7,219).